Kinetic analysis and general features of thermoluminescence of B2O3-Li2O-ZnF2 glass. (May 2017) - Thomas, Sunil; Chithambo, M.L.
Abstract: The intention of this study is to explore the thermoluminescence of beta irradiated B2 O3 -Li2 O-ZnF2 glass. The glow-curve corresponding to 200 Gy shows three peaks; two weak-intensity peaks at 60 and 243 °C and a more prominent one at 118 °C, when measured at 1 °C/s. The dose response of the main peak at 118 °C was found to be sublinear in the range 200–1000 Gy. Regarding the kinetic analysis of the main peak, the activation energy of the corresponding electron trap was evaluated as 0.96 eV and the frequency factor as ∼10 11 s −1 . It is proposed that the thermoluminescence in B2 O3 -Li2 O-ZnF2 glass is due to recombination of electrons, thermally released from Zn + ionic defect sites, with the holes at boron-oxygen hole centres. Highlights: Thermoluminescence properties of B2 O3 -Li2 O-ZnF2 glass are reported. Kinetic parameters including activation energy and frequency factor are reported. The dose response in the range 200–1000 Gy is shown. A possible mechanism for thermoluminescence is described.